1981
DOI: 10.1159/000182388
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-Associated Hepatoma in a Hemodialysis Patient

Abstract: A patient on hemodialysis treatment developed hepatocellular carcinoma (HCC) after long-term therapy with androgenic anabolic steroids. The tumor progressed very rapidly, and there was no evidence of regression despite discontinuation of the drug. In view of the evidence of an increased incidence of malignancy in patients with chronic uremia and hemodialysis, and of the higher frequency of HCC correlated to treatment with C17-alkylated anabolic steroids, it is necessary to further evaluate the efficiency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…The androgen preparation was nandrolone decanoate, which is efficacious and without appreciable side effects [3,11]. Liver dysfunction, peliosis hepatis and hepatocellular carcinoma have been reported in patients receiving 17-alkyiated androgens [12][13][14][15][16], Nandrolone decanoate is not a 17-alkylated androgen and no cases of hepatic injury have been described with the use of this drug [17][18][19][20][21][22],…”
Section: Introductionmentioning
confidence: 99%
“…The androgen preparation was nandrolone decanoate, which is efficacious and without appreciable side effects [3,11]. Liver dysfunction, peliosis hepatis and hepatocellular carcinoma have been reported in patients receiving 17-alkyiated androgens [12][13][14][15][16], Nandrolone decanoate is not a 17-alkylated androgen and no cases of hepatic injury have been described with the use of this drug [17][18][19][20][21][22],…”
Section: Introductionmentioning
confidence: 99%
“…Lower level of serum albumin in this study is attributed to less intake of protein than the commonly recommended protein intake. It is reported that use of androgen induces liver dysfunction, peliosis hepatis and hepatoma when 17-alkylated androgen was used 22 25 ) , but such liver damages were not reported when nandrolone decanoate as a derivative of 19-nortestosterone was used 3 , 8 , 9 , 26 , 27 ) . No finding of liver dysfunction was observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Tumores hepáticos têm sido associados com o uso de esteróides anabolizantes em indivíduos submetidos a tratamento clínico com estas drogas [74][75][76][77][78][79][80] . Estes tumores são geralmente benignos 75,77,78,80 , mas têm sido observadas lesões malignas associadas com o uso dessas drogas 74,79,80 . A possível relação causa-efeito desta associação entre o uso de esteróides e o desenvolvimento de tumores é reforçada pelo relato da regressão do tumor após interrupção do tratamento com esteróides 76 .…”
Section: Efeitos Adversosunclassified
“…Tem havido relatos de que as provas de função hepática estão inalteradas com o uso de esteróides em alguns estudos envolvendo treinamento 31,36,41,48 e alteradas em outros estudos semelhantes 45,47 e em exames realizados em atletas que sabidamente estavam em uso de esteróides anabolizantes 11,48,59 . Contudo, as lesões de peliose hepática e tumores hepáticos nem sempre produzem anormalidades nesses exames 65,[74][75][76][77]80 e alguns autores sustentam que são necessárias cintilografias hepáticas, ultra-sonografias ou tomografias computadorizadas para este diagnóstico 74,75,83 .…”
Section: Efeitos Adversosunclassified